Critical Review: Fostering Entrepreneurial Mindsets in Deep Tech Disciplines - Utami Tunjung Sari; Ascasaputra Aditya; Bhenu Artha (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This article aims to review the research conducted by Corina Pacher and Martin Glinik from Graz University of Technology, which presents an educational toolkit designed to integrate entrepreneurship education into higher education institutions (HEIs) within Deep Tech-related disciplines. The article employs a critical review method. The work addresses the crucial gap between theoretical knowledge and the practical application of entrepreneurial competencies among engineering students, academic staff, and non-academic personnel. While the paper engages with an increasingly relevant topic and proposes a hands-on pedagogical solution, it demonstrates significant limitations in methodological rigor, empirical validation, and theoretical depth, which substantially reduce its contribution to international scholarship.